Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Pegawai Pada BPMPT Provinsi Jawa Barat - Saftara, Indra (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
The main problem in this research is the performance of employees of Investment Board and Integrated Licensing (BPMPT) West Java Province felt very less. The problem is caused by the absence of optimal transformational leadership. The approach used in this research is descriptive method of analysis that describes social phenomena by examining the influence of Transformational Leadership (X) on Employee Performance (Y). This research uses a quantitative analysis technique through path analysis which is intended to know the influence of variables of Transformational Leadership toward Employee Performance, either simultaneously or partially. The results showed that Transformational Leadership affects Employee Performance on the Investment Board and Integrated Licensing (BPMPT) of West Java Province. The simultaneous effect of transformational leadership variables on employee performance was 82%. The value is strong enough. While other influences that are not examined or epsilon affect employee performance of 17.2%. Partially, Transformational Leadership is tested in influencing employee performance that is covering an aspect of ideal influence equal to 6,5%, inspirational aspect motivation 21%, aspect of intellectual simulation equal to 27,4%, aspect of individual consideration 27,9% and other variable 17, 2%. The conclusion that transformational leadership is a very important factor in influencing the performance of the employees of the Investment and Investment Permit (BPMPT) of West Java Province. Optimize the performance of key personnel is done through transformational leadership variables. The results of this study can be concluded that the transformational leadership either simultaneously or partially affect the performance of employees of the Investment and Integrated Licensing Agency (BPMPT) West Java Province.